Respostas
respondido por:
1
y = - 2x
× - ( -2x) = -9
x+2x=-9
3x=-9
x=-3
× - ( -2x) = -9
x+2x=-9
3x=-9
x=-3
nataliecampos:
y = -2 × -3 = 6
respondido por:
1
Oi novamente,
Resolução
{ 2x + y = 0
{ x - y = - 9
3x = - 9
x = - 9/3
x = - 3
x - y = - 9
- 3 - y = - 9
- y = - 9 + 3
- y = - 6 . ( - 1 )
y = 6
S = { - 3 , 6 }
Espero ter ajudado e bons estudos !
Resolução
{ 2x + y = 0
{ x - y = - 9
3x = - 9
x = - 9/3
x = - 3
x - y = - 9
- 3 - y = - 9
- y = - 9 + 3
- y = - 6 . ( - 1 )
y = 6
S = { - 3 , 6 }
Espero ter ajudado e bons estudos !
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás